Epithelial–mesenchymal transition in organ fibrosis development: current understanding and treatment strategies. Issue 1 (8th April 2022) - Liu, Lexin; Sun, Qizhe; Davis, Frank; Mao, Jianhua; Zhao, Hailin; Ma, Daqing
Abstract: Organ fibrosis is a process in which cellular homeostasis is disrupted and extracellular matrix is excessively deposited. Fibrosis can lead to vital organ failure and there are no effective treatments yet. Although epithelial–mesenchymal transition (EMT) may be one of the key cellular mechanisms, the underlying mechanisms of fibrosis remain largely unknown. EMT is a cell phenotypic process in which epithelial cells lose their cell-to-cell adhesion and polarization, after which they acquire mesenchymal features such as infiltration and migration ability. Upon injurious stimulation in different organs, EMT can be triggered by multiple signaling pathways and is also regulated by epigenetic mechanisms. This narrative review summarizes the current understanding of the underlying mechanisms of EMT in fibrogenesis and discusses potential strategies for attenuating EMT to prevent and/or inhibit fibrosis. Despite better understanding the role of EMT in fibrosis development, targeting EMT and beyond in developing therapeutics to tackle fibrosis is challenging but likely feasible.